Measuring gene flow in barley fields under Icelandic sub-arctic conditions using closed-flowering varieties - Jónatan Hermannsson 1946-; Þórdís Anna Kristjánsdóttir 1953-; Tryggvi Sturla Stefánsson 1982-; Jón Hallsteinn Hallsson 1976- (2010)
Genetic engineering is becoming an important tool for the improvement of plants for various forms of production. As varieties are developed for both food and non-food use different production lines must be kept separate. For good management practices of different lines an understanding of gene-flow is essential. Barley has been proposed to be an ideal plant species for genetic engineering as it has a low frequency of crossfertilization and limited seed dispersal. In the present study, pollen-mediated exchange of genetic material between non-transgenic closed-flowering barley variants was examined in experimental plots under sub-arctic conditions in Iceland. The pollen-mediated dispersal was studied using the barley varieties Golden Promise and Ven, as pollen donor and acceptor, respectively. Only two hybrid plants were identified from a total of 700,000 screened plants giving a hybridization frequency of 0.0003%. It is concluded that adequate isolation distances and good management practices should suffice to prevent cross-fertilization between different lines of barley. Eftir því sem erfðatækni vex fiskur um hrygg við kynbætur á plöntum, bæði til fæðu- og iðnaðarframleiðslu, verður sífellt mikilvægara að halda kynbótalínum aðskildum. Við ræktun á kynbótaefniviði er því nauðsynlegt að þekkja vel genaflæði í þeirri tegund sem verið er að vinna með hverju sinni. Talið er að bygg henti vel til kynbóta með erfðatækni þar sem það er að langmestu leyti sjálffrjóvga og dreifing á fræi takmörkuð. Í rannsókninni sem hér er kynnt var flutningur erfðaefnis milli byggyrkja með lokuð blóm rannsakaður í tilraunareitum við íslenskar aðstæður. Byggyrkin Golden Promise, sem þjónaði hlutverki frjógjafa, og Ven, sem þjónaði hlutverki frjóþega, voru ræktuð hlið við hlið í tilraunareitum. Skoðaðir voru 700.000 einstaklingar og fundust einungis tveir blendingar sem jafngildir 0,0003%. Því má telja að alfarið sé hægt að koma í veg fyrir flutning erfðaefnis milli byggyrkja með því að hafa lágmarksfjarlægð milli akra og viðhafa góð ...